Tell It your way: technology-mediated human-human multimodal communication - Cardoso, Helena Maria do Nascimento (2022)
Communication plays a pivotal role in our daily lives. With the advances of technology, we are now able to use it to communicate with others at a distance. However, while in human-human communication, we are able to adjust how we pass a message based on our context and the perceived context of the receiver, this is harder to attain when we use technology through popular choices, such as messaging tools. In fact, most of these tools, such as Whatsapp or Messenger, provide some degree of flexibility regarding how a message is sent (e.g., text, audio, image), but the receiver is limited to receiving it in the chosen format by the sender. In this regard, providing more flexibility in such technology-mediated communication scenarios might foster increased adaptability of these tools to multiple user abilities and contexts and provide essential alternatives for those with some disability (e.g., aphasia, blindness). The work presented here adopts a user-centered approach to design, develop, and evaluate the first proof-of-concept for a multi-platform and multimodal messaging system that enables users to adopt several messaging formats interchangeably regardless of the original message format. To this end, the first set of requirements was defined based on the feedback obtained from 69 potential users of such tools and on the definition of representative personas and scenarios. These provided the grounds for designing and developing high-fidelity mockups that validated the proposed paradigm and refined the initial requirements. In the next iteration, and based on the outcomes of the mockup evaluation, the first version of a novel messaging tool, Tell It Your Way, was developed, integrating several message modality conversion features. At its current stage, evaluation results show a good level of usability and user satisfaction and establish Tell It Your Way as promising ground for further evolving the research on multimodal technology-mediated communication.